2018
DOI: 10.3390/ijms19041162
|View full text |Cite
|
Sign up to set email alerts
|

CA 19-9 Pancreatic Tumor Marker Fluorescence Immunosensing Detection via Immobilized Carbon Quantum Dots Conjugated Gold Nanocomposite

Abstract: The clinical detection of carbohydrate antigen 19-9 (CA 19-9), a tumor marker in biological samples, improves and facilitates the rapid screening and diagnosis of pancreatic cancer. A simple, low cost, fast, and green synthesis method to prepare a viable carbon quantum dots/gold (CQDs/Au) nanocomposite fluorescence immunosensing solution for the detection of CA 19-9 was reported. The present method is conducted by preparing glucose-derived CQDs using a microwave-assisted method. CQDs were employed as reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(46 citation statements)
references
References 45 publications
0
39
0
3
Order By: Relevance
“…Molecules 2020, 25, combining with other types of nanoparticles [21,[36][37][38][39]. Application of heteroatoms, such as nitrogen and sulfur, helps to create new surface states which results in enhanced photoluminescence (PL) properties, especially increased photostability and quantum yield [10,24,35].…”
Section: Fouriertransform Infrared Spectroscopy (Ftir) and Nuclear Mamentioning
confidence: 99%
See 3 more Smart Citations
“…Molecules 2020, 25, combining with other types of nanoparticles [21,[36][37][38][39]. Application of heteroatoms, such as nitrogen and sulfur, helps to create new surface states which results in enhanced photoluminescence (PL) properties, especially increased photostability and quantum yield [10,24,35].…”
Section: Fouriertransform Infrared Spectroscopy (Ftir) and Nuclear Mamentioning
confidence: 99%
“…The parameter is almost twice lower for water, acetone, and ACN, and a very small shift of the peak maximum is noticeable. Thus, it can be concluded that the nanomaterials may be applied in various applications and media of various hydrophility, which is important in the field of diagnostics, and from this point of view is a desirable feature [17][18][19][20][21][22][23]. Our previous research showed that the bottom-up CQD synthesis routes with in situ doping enables the preparation of nanodots with the maximal QY up to 13%, which may be insufficient in some applications [44].…”
Section: Spectroscopic Properties Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Such a phenomenon is called the quantum confinement effect [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Quantum dots may be applied in bioimaging and biodiagnostics [ 16 , 17 , 18 , 19 ]. Various types of these nanomaterials were successfully used for this purpose such as CdS, CdSe, CdTe, MoS 2 or PbS.…”
Section: Introductionmentioning
confidence: 99%